Climate Change Projections of Temperature Over the Coastal Area of China Using SimCLIM - Wang, Xiaoli; Hou, Xiyong; Piao, Yingchao; Feng, Aiqing; Li, Yinpeng (Frontiers in Environmental Science, 2021)
Facing the western Pacific Ocean and backed by the Eurasian continent, the coastal area of China (hereafter as CAC) is sensitive and vulnerable to climate change due to the compound effects of land-ocean-atmosphere, and thus is prone to suffer huge climate-related disaster losses because of its large population density and fast developed economy in the context of global warming. Here in this study the near- (2040), mid- (2070) and long-future (2100) mean, minimum and maximum temperature (Tmean, Tmin and Tmax) projections based on the statistic downscaling climate prediction model (SimCLIM) integrated with 44 General Circulation Models (GCMs) of CMIP5 under three representative concentration pathway (RCP4.5, RCP6.0 and RCP8.5) scenarios are evaluated over CAC and its sub-regions. Multi-model ensemble of the selected GCMs demonstrated that there was a dominating and consistent warming trend of Tmean, Tmin and Tmax in the Chinese coastal area in future. Under RCP4.5, RCP6.0 and RCP8.5 scenarios, the annual temperature increase was respectively projected to be in the range of 0.8–1.2 °C for 2040, 1.5–2.7 °C for 2070 and 1.6–4.4 °C for 2100 over the entire CAC. Moreover, a spatial differentiation of temperature changes both on the sub-regional and meteorological station scales was also revealed, generally showing an increment with “lower in north and higher in south” for annual average Tmean but “higher in north and lower in south” for Tmin and Tmax. An obvious lower increase of Tmean in the hotter months like July and August in south and a significant sharper increment of Tmin and Tmax in the colder months such as January, February and December in north were expected in future. Results derived from this study are anticipated to provide insights into the future temperature changes and also assists in the development of target climate change mitigation and adaptation measures in the coastal area of China.